Fast Zero Migration Algorithm for Near-Field Sparse MIMO Array Grating Lobe Suppression - Zhu, Rongqiang; Zhou, Jianxiong; Chen, Shiqi; Ding, Haiyang (IEEE transactions on antennas and propagation, 2025)
Under near-field conditions, spatial undersampling leads to grating lobes in the sparse multiple-input multiple-output (MIMO) array results. A fast zero migration algorithm is developed in this communication for suppressing the grating lobes. In our method, resampling in the wavenumber domain is first achieved on the received data, and then, the fast inverse Fourier transform (FT) and compensation on the image domain is leveraged for achieving zero migration of transceiver array. By applying apodization on the zero migration result, zero spreading is equivalently achieved and thus alleviate the influence of grating lobe spreading under near-field conditions and avoid the ghosts in the imaging results. Benefit from its fast FT-based processing scheme, the method achieves a reduction in computational complexity from O( N ^{4} ) to O( N ^{3} logN). Both simulated and measured data validate the superiority of the method in effectively suppressing grating lobes and improving the processing efficiency.